A Study of Schistosomiasis Prevalence and Risk of Snail Presence Spatial Distributions Using Geo-Statistical Tools - Guimarães, Ricardo J.P.S.; Fonseca, Fernanda R.; Dutra, Luciano V.; Freitas, Corina C.; Oliveira, Guilherme C.; Carvalho, Omar S. (IntechOpen, 2012)
None